Primary bile reflux gastritis versus Helicobacter pylori gastritis: a comparative study - Enaase A.M.E Barakat; Neven F Abbas; Nashwa Y El-Kholi (SpringerOpen, 2018)
Background Bile reflux gastritis (BRG) is a common disorder, with few data on its pathophysiology and clinical course, whereas Helicobacter pylori is the well-known, commonest cause of chronic gastritis. Aim The aim of this study was to compare between BRG and H. pylori-related gastritis, as regards demographic data, comorbid conditions, and pattern of upper gastrointestinal involvement. Patients and methods It included 130 patients with endoscopic features of gastritis, subdivided into three groups: group A with BRG (56 patients); group B with H. pylori gastritis (58 patients); group C with gastritis in the presence of both H. pylori and bile reflux (16 patients). Statistical analysis was made to compare between the three groups as regards demographic data, history, and examination findings including endoscopic findings. Results BRG is more common among younger age (21-30 years) and elderly patients (71-80 years), whereas H. pylori gastritis is more common in patients in the middle age group (31-60 years), the female/male ratio was 1.5 : 1 in patients with BRG, 1 : 1 in H. pylori gastritis. Nausea was the commonest symptom in patients with BRG (69.6%), whereas epigastric pain/discomfort was the commonest symptom (77.6%) in H. pylori gastritis. Diabetes was found to be more common in patients with H. pylori gastritis (29.3%) followed by BRG (26.8%), whereas obesity was more common in patients with BRG (76.8%) followed by H. pylori gastritis (65.5%). Endoscopy showed antral gastritis in cases with BRG (57.1%), pangastritis in H. pylori and mixed etiology gastritis (60.3 and 68.8%, respectively), reflux esophagitis in both BRG and H. pylori gastritis (41.1 and 44.8%, respectively), higher than mixed etiology gastritis (25%). Endoscopic Barrett's mucosa was diagnosed in 10.7% of cases with BRG and 12.1% of cases with H. pylori gastritis. Duodenitis, duodenal erosions, or ulcerations were more common in cases with mixed etiology gastritis (62.5%), than in H. pylori gastritis (24.1%), followed by BRG (14.3%). Conclusion BRG is a common, underdiagnosed condition, with distinct clinical and endoscopic features from H. pylori gastritis.